Rendering happiness metaphors: a cognitive analysis from persian into English - Safarnejad, Fatemeh; Imran-Ho-Abdullah,; Norsimah Mat Awal, (Penerbit UKM, 2013)
Translation of metaphorical expressions is a major challenge in literary translation and has attracted the attention of translation researchers and linguists alike. The aim of this paper is to examine the translation of emotive metaphorical expressions of happiness from Persian to English in the Persian novel “Savushun” written by Simin Daneshvar. To achieve this aim, emotive metaphorical expressions relating to happiness from the source text and two target texts were collected. Subsequently, the conceptual metaphors underlying the metaphorical expressions in the source text and the target texts were investigated based upon the metaphor identification procedures (MIP), proposed by the Pragglejaz group (2007) and general framework of the conceptual metaphor theory (CMT). This paper attempts to identify the strategies used in the translation so that the translational equivalences of these metaphorical expressions were identified in the target texts. The conceptual metaphors of the translation were identified and compared with the conceptual metaphors in the source text. Preliminary results of the study revealed the nature of both similarities and differences in the conceptual metaphors of the source text to the target texts. The similarities are mostly attributed to the universality metaphor, whereas the differences are related to two different concepts and different culture in the translation of metaphors.